Numerical estimation of shallow water effect on multipurpose amphibious vehicle resistance (Journal of Naval Architecture and Marine Engineering, 2017)
This research paper investigated the hydrodynamic resistance of Multipurpose Amphibious Vehicles (MAV) due to navigate in low water depth numerically. This type of vehicle and other coastal floating vehicles encounter the problem of a small under keel clearance with river bed. The proper estimation of ship resistance and squat is influence largely on the power calculation in the design stage. The present work describes the effect of shallow water on the Multipurpose Amphibious Vehicles (MAV) resistance at different speed using Computational Fluid Dynamics (CFD) techniques. A comparison in the drag on the hull is illustrated between depth restriction and infinite depth water. This paper provides a wide introduction into the problems of modelling of the restricted water depth effects on the ship behaviour, specifically hydrodynamic resistance and squat using CFD which is applied by ANSYS-CFX14.0.